2022
DOI: 10.1186/s41077-022-00237-w
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation-based training during hospital relocation: a controlled intervention study

Abstract: Background During hospital relocations, it is important to support healthcare professionals becoming familiar with new settings. Simulation-based training seems promising and in situ simulation has been suggested as a beneficial educational tool to prepare healthcare professionals for relocation. This study aimed to investigate the impact of a simulation-based training intervention on health professionals´ readiness to work in their new environment, as well as investigate sick leave before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…An analysis of the literature citing Brazil’s translational simulation article [ 11 ] demonstrates diverse applications of the concept. These include translational simulation to prepare health services for the COVID-19 pandemic [ 18 30 ], for hospital relocation or physical space testing [ 31 ], for clinical pathway or process testing [ 32 39 ], and for shaping culture and teamwork in healthcare settings [ 35 , 40 46 ]. Other citing literature has included conceptual discussions and review articles [ 47 51 ], as well as efforts to develop methods and tools for ‘translational simulation in action’ [ 16 , 32 , 52 ].…”
Section: Exploring Translational Simulation In Practicementioning
confidence: 99%
“…An analysis of the literature citing Brazil’s translational simulation article [ 11 ] demonstrates diverse applications of the concept. These include translational simulation to prepare health services for the COVID-19 pandemic [ 18 30 ], for hospital relocation or physical space testing [ 31 ], for clinical pathway or process testing [ 32 39 ], and for shaping culture and teamwork in healthcare settings [ 35 , 40 46 ]. Other citing literature has included conceptual discussions and review articles [ 47 51 ], as well as efforts to develop methods and tools for ‘translational simulation in action’ [ 16 , 32 , 52 ].…”
Section: Exploring Translational Simulation In Practicementioning
confidence: 99%
“…17 Consequently, the utilisation of simulation-based team training emerges as a promising approach to mitigating sick leave within the healthcare professional community. 18 Simulation-based team training can be used to imitate real-life scenarios from clinical settings, in which a scene of conditions is created to mirror authentic situations. 19 20 Additionally, simulation can help healthcare professionals become conscious of their abilities and develop skills in a safe learning environment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In a more recent study, it was suggested that simulation-based training might have a preventative impact on sick leave 17. Consequently, the utilisation of simulation-based team training emerges as a promising approach to mitigating sick leave within the healthcare professional community 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation